UNCONVENTIONAL FOOD PLANTS (UFP) FOUND IN SANTA CATARINA STATE - Thábata Cristina Faxina Aguiar; Aline Nunes; Mariangela de Souza Damasceno (Universidade do Estado do Rio Grande do Norte, 2020)
This work identified unconventional food plants (UFP) in a rural area in Santa Catarina and described their nutritional and therapeutic properties. Data were collected in December 2016 in an area of "‹"‹agroecological garden and forest edge. All species founded were identified and had characteristics such as part used, habit, origin, use and nutraceutical potential analyzed according to specialized literature. Were identified 44 species from 29 families, the most frequent being Asteraceae. 75% of them have more than one part indicate for use. 81.32% of the species are herbaceous and 56.82% are exotic species. 54.54% of the species have another indication of use. The nutraceutical description of 88.36% of species was found in the literature although often incomplete. It is concluded that the area has a huge nutritional and medicinal potential, however, further studies are needed to consolidate them as common food options, contributing to a more diverse and nutritious diet.